Mass catering establishments – concept, classification, legal status - Fornalik, Aneta (Przegląd Prawa Rolnego, 2023)
The aim of the considerations was to determine the content of the concept of “mass catering establishments,” to classify these establishments and to determine their legal status. In pursuing the objective thus defined, the various concepts that have been analysed include: “establishment,” “mass catering establishment,” “open type mass catering establishment,” “closed type mass catering establishment” and “food establishment.” Under food law, a distinction may be made between an open-type and a closed-type mass catering establishment. This distinction is somewhat simplified, as a closed-type mass catering establishment represents only a fragment of the activities of a given entity. In conclusion of the conducted considerations, among other things, attention is drawn to the heterogeneity of the discussed concept under national and EU laws, and to the diversity of other concepts related to the operation of mass catering establishments. Attempting to embrace all mass catering establishments under a single definition is a risky endeavour, given that each of such establishments exhibits a certain specificity in its food business. Furthermore, food law does not regulate the operation of individual units in the capacity of mass catering establishments.